2017
DOI: 10.1088/1361-648x/aa839d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu doping on the electronic structure and magnetic properties of MnCo2O4nanostructures

Abstract: Reported here are the results and their analysis from our detailed investigations of the effects of Cu doping ([Formula: see text]) on the electronic structure and magnetic properties of the spinel [Formula: see text]O. A detailed comparison is given for the [Formula: see text] and [Formula: see text] cases for both the bulk-like samples and nanoparticles. The electronic structure determined from x-ray photoelectron spectroscopy and Rietveld analysis of x-ray diffraction patterns shows the structure to be: ([F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 82 publications
2
37
1
Order By: Relevance
“…For this sample weak hysteresis is still observed, thus indicating the antiferromagnetic nature of this sample at 300 K. 43,49 This type of behavior is observed for Cu substituted spinel MnCo 2Àx Cu x O 4 (0 # x # 0.2) nanostructures with the samples x $ 0.1 having the coercivity H c and remanence M r close to 0. 50 In the Mn x Zn 1Àx Co 2 O 4 the non-magnetic divalent Zn 2+ ions tend to occupy tetrahedral (A) sites and thereby force the incoming Mn ions to octahedral (B) sites due to their favoritism by polarization effect. 30 In general, spinel type cobalt-based oxides contain high spin Co 2+ (S ¼ 3/2) in the tetrahedral site and low spin diamagnetic Co 3+ (S ¼ 0) in the octahedral site; magnetic ions in the sub lattices are arranged antiparallel to their four neighboring ions resulting in antiferromagnetic behavior of the material.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…For this sample weak hysteresis is still observed, thus indicating the antiferromagnetic nature of this sample at 300 K. 43,49 This type of behavior is observed for Cu substituted spinel MnCo 2Àx Cu x O 4 (0 # x # 0.2) nanostructures with the samples x $ 0.1 having the coercivity H c and remanence M r close to 0. 50 In the Mn x Zn 1Àx Co 2 O 4 the non-magnetic divalent Zn 2+ ions tend to occupy tetrahedral (A) sites and thereby force the incoming Mn ions to octahedral (B) sites due to their favoritism by polarization effect. 30 In general, spinel type cobalt-based oxides contain high spin Co 2+ (S ¼ 3/2) in the tetrahedral site and low spin diamagnetic Co 3+ (S ¼ 0) in the octahedral site; magnetic ions in the sub lattices are arranged antiparallel to their four neighboring ions resulting in antiferromagnetic behavior of the material.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…20 Recent studies reveal that MnCo 2 O 4 nanoparticles exhibit memory and aging effects, spinglass like characteristics below the freezing point T F ¼ 144:8 K (with zν ¼ 6:01 and τ o 6:18 Â 10 À15 s) together with a finite size scaling of T C (T C (d) ¼ T C (1)[1 À (ξ 0 =d) λ ], λ ¼ 0:75 + 0:15, and ξ 0 ¼ 1:4 + 0:3 nm). 17,19,21 Moreover, a significant reduction of T C (167 K) was noticed with the incorporation of Jahn-Teller active ion Cu at the octahedral Co(B) sites of MnCo 2 O 4 . 19 On the other hand, Bhowmik and Ranganathan reported that the substitution of 50 at.…”
mentioning
confidence: 96%
“…17,19,21 Moreover, a significant reduction of T C (167 K) was noticed with the incorporation of Jahn-Teller active ion Cu at the octahedral Co(B) sites of MnCo 2 O 4 . 19 On the other hand, Bhowmik and Ranganathan reported that the substitution of 50 at. % of Ru at the Mn site leads to a further decrease of T C (100 K) together with the signatures of pinning effects in domain wall dynamics.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Even though the authors owed it to domain wall pinning effect, it was not confirmed by further evidences. In the counterpart Mn 1 − x Cu x Co 2 O 4 , two magnetic phases can be identified from the hysteresis loops . Therefore, the observed high coercivity in Mn 0.5 Ru 0.5 Co 2 O 4 may not be solely due to the domain wall pinning effect, but the interaction among different magnetic phases.…”
Section: Introductionmentioning
confidence: 96%